Smart city initiatives in the context of digital transformation scope, services and technologies - Tomičić-Pupek, Katarina; Pihir, Igor; Tomičić Furjan, Martina (2019)
Digital transformation is an emerging trend in developing the way how the work is being done, and it is present in the private and public sector, in all industries and fields of work. Smart cities, as one of the concepts related to digital transformation, is usually seen as a matter of local governments, as it is their responsibility to ensure a better quality of life for the citizens. Some cities have already taken advantages of possibilities offered by the concept of smart cities, creating new values to all stakeholders interacting in the living city ecosystems, thus serving as examples of good practice, while others are still developing and growing on their intentions to become smart. This paper provides a structured literature analysis and investigates key scope, services and technologies related to smart cities and digital transformation as concepts of empowering social and collaboration interactions, in order to identify leading factors in most smart city initiatives.
Digitalna transformacija je novi trend u načinu razvoja obavljanja posla, kako u privatnom, tako i u javnom sektoru, bez obzira na industriju, odnosno područje rada. "Pametni" se gradovi, kao jedan od koncepata u okviru digitalne transformacije, obično povezuju s lokalnom upravom, s obzirom da je njihova odgovornost osigurati bolju kvalitetu života građana. Neki su gradovi već iskoristili mogućnosti koje pruža koncept “pametnog grada”, stvarajući vrijednost za sve dionike živućeg gradskog eko-sustava, pa se mogu smatrati primjerima dobre prakse. Drugi se, pak, gradovi tek usmjeravaju i razvijaju prema ostvarivanju koncepta "pametnog grada". U ovom se radu pruža strukturirani pregled literature i analiziraju opseg, usluge i tehnologije, povezani s “pametnim gradovima” te digitalnom transformacijom, kao konceptima, usmjerenim na jačanje društvene interakcije i suradnje, a s ciljem utvrđivanja vodećih čimbenika u većini inicijativa "pametnih gradova".
Bibliografija: 58 jed.
Summary ; Sažetak.
Keywords: Digitalne tehnologije -- Informacijsko-komunikacijske tehnologije -- Gradovi